The Role of Village Unit Cooperatives in Increasing Community Income in Dolok Tolong Village - Susi Sulastri Simaremare (Institute of Computer Science (IOCS), 2019)
KUD is a multi-business cooperative consisting of villagers and located in rural areas. KUD Saroha Nauli Credit Union is an economic institution in the Dolok Tolong. This study aims to determine how the role of Saroha Nauli Credit Union Cooperative in increasing members 'income, the obstacles faced in increasing members' income and the solutions provided by Saroha Nauli Credit Union Cooperative to overcome the problem. This research is qualitative and uses data collection techniques through interviews, questionnaires and documentation. The population in this study were 5 people. Sampling used in the form of saturated sampling with a sample adjusted for the amount of land owned by members, namely members who have ± 1 hectare of land/village. The results showed that the KUD Saroha Nauli Credit Union had a role in increasing the income of its members in particular. This is seen from the income analysis of members. From the analysis carried out the members' income increased from before becoming a member. Constraints faced by the KUD Saroha Nauli Credit Union in increasing members' income is the presence of several members who did not attend counseling / education carried out by the KUD Saroha Nauli Credit Union and another obstacle was the lack of material and non-material capital. The solution is given by KUD Saroha Nauli Credit Union to overcome the constraints of the absence of members by sanctions or fines for the absence of members and gifts for those who are diligent in meeting members.